PROFIL KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DALAM PROSES PEMBELAJARAN DARING PADA MATERI MATRIK - Jannah, Laila Faiqotul; Al Ayubi, Sholahudin; Mahmudah, Muhlisatul (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2022)
This study aims to determine how the profile of students' mathematical communication skills in class XI IPA MA Ma'arif Ambulu in the online learning process on matrix material. This research is a descriptive study with a qualitative approach. The subjects in this study were 35 students of class XI IPA MA Ma'arif Ambulu. Whereas for a sample of 9 students. The data from this research were taken using interview, documentation and test methods. The results showed and proved that from a sample of 9 students of class XI IPA MA Ma'arif Ambulu regarding students' mathematical communication skills there was an increase after the online learning process. From the high level which initially had 3 students to 4 students, 3 students with moderate abilities increased to 4 students, and 3 students with low abilities decreased to 1 student. The online learning process with the WhatsApp group carried out regarding the profile of students' mathematical communication skills can be described accurately. Keywords:Communication Skills, Online Learning